PERAN ORGAN TUNGGAL DALAM ACARA BARALEK DI PADANG - Yensharti Yensharti (Imaji, 2007)
The research aims at studying the performance of solo organ nowadays popular among Minangkabau people, especially in the wedding ceremony (Baralek) in Padang. The performance is of a new music genre, which in the last two decades has become more and more well-known in the urban area as well as in the rural one. At the beginning, the performance was particularly organized in hotels. A year later in 1984, it was performed in private houses and culminating in 2000 many new solo organ groups emerged in Padang. Malam Bainai and Alek Nak Mudo serve as the main songs played in the traditional procession of welcoming and escorting the bridal couple, while Anak Daro and Marapulai are played when they go to the nuptial seat and when they leave it during the Baralek. The existence of solo organ performance in the ceremony plays important roles as emotional expressions, personal entertainment, symbols, communication, social integrity, physical reaction or productivity stimulation and serves the ritual function. Key words: solo organ, Baralek music